A generalized quantitative antibody homeostasis model: regulation of B‐cell development by BCR saturation and novel insights into bone marrow function. Issue 2 (17th February 2017) - Prechl, József
Abstract : In a pair of articles, we present a generalized quantitative model for the homeostatic function of clonal humoral immune system. In this first paper, we describe the cycles of B‐cell expansion and differentiation driven by B‐cell receptor engagement. The fate of a B cell is determined by the signals it receives via its antigen receptor at any point of its lifetime. We express BCR engagement as a function of apparent affinity and free antigen concentration, using the range of 10 −14 –10 −3 m for both factors. We assume that for keeping their BCR responsive, B cells must maintain partial BCR saturation, which is a narrow region defined by [Ag]≈ K D . To remain in this region, B cells respond to changes in [Ag] by proliferation or apoptosis and modulate K D by changing BCR structure. We apply this framework to various niches of B‐cell development such as the bone marrow, blood, lymphoid follicles and germinal centers. We propose that clustered B cells in the bone marrow and in follicles present antigen to surrounding B cells by exposing antigen captured on complement and Fc receptors. The model suggests that antigen‐dependent selection in the bone marrow results in (1) effector BI cells, which develop in blood as a consequence of the inexhaustible nature of soluble antigens, (2) memory cells that survive in antigen rich niches, identified as marginal zone B cells. Finally, the model implies that memory B cells could derive survival signals from abundant non‐cognate antigens.